2020
DOI: 10.1002/jwmg.21812
|View full text |Cite
|
Sign up to set email alerts
|

Hunting Activity Effects on Roost Selection by Male Wild Turkeys

Abstract: Roosting is an important component of wild turkey (Meleagris gallopavo; turkey) ecology as roosts provide security from predators and inclement weather. Males call (gobble) from roosts during the reproductive season, and roost locations are important for maximizing access to females and transmission of calls across the landscape, while also minimizing predation risk. Spring hunting of male turkeys occurs during the reproductive season, and hunting activity influences male behaviors and calling. Because roost s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…We removed water and infrastructure from our analysis as both were not usable by broods. We used 30‐m resolution imagery from United States Geological Survey (USGS) Landsat–8 Operational Land Imager to compute a normalized difference vegetation index (NDVI) in ArcMap 10.3 (ESRI, Redlands, CA, USA) as an index of vegetation density (Wakefield et al 2020). Measurements of NDVI allowed us to understand sparseness of vegetation, which has been shown to influence maneuverability, concealment, and foraging ability for poults (Williams et al 1970, Healy 1985).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We removed water and infrastructure from our analysis as both were not usable by broods. We used 30‐m resolution imagery from United States Geological Survey (USGS) Landsat–8 Operational Land Imager to compute a normalized difference vegetation index (NDVI) in ArcMap 10.3 (ESRI, Redlands, CA, USA) as an index of vegetation density (Wakefield et al 2020). Measurements of NDVI allowed us to understand sparseness of vegetation, which has been shown to influence maneuverability, concealment, and foraging ability for poults (Williams et al 1970, Healy 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of NDVI allowed us to understand sparseness of vegetation, which has been shown to influence maneuverability, concealment, and foraging ability for poults (Williams et al 1970, Healy 1985). Within each buffer, we estimated the proportion of each landcover type and calculated mean NDVI to evaluate habitat use by broods (Pettorelli et al 2005, Wakefield et al 2020). We binned each buffer based upon number of revisitations that occurred in it (low = 0–10, low/moderate = 11–20, moderate = 21–30, high = ≥31) and used a 1‐way analysis of variance to determine if differences existed in revisitation relative to landcover type and mean NDVI.…”
Section: Methodsmentioning
confidence: 99%
“…Additional factors may confound turkey distribution and site abandonment, such as disturbance from managed logging (Fredericksen et al, 2000 ) or hunting pressure. Recent studies have demonstrated that hunting activities and hunter behavior may influence male turkey movements (Gerrits et al, 2020 ), roosting behaviors (Wakefield et al, 2020a ), and daily gobbling activity (Chamberlain et al, 2018 ; Wightman et al, 2019 ), but these conclusions have not been universal (Collier et al, 2017 ; Gross et al, 2015 ). Without a thorough understanding of the influence of hunting activities on individual turkey behaviors in our study system, we surmise that detection of a different individual during a subsequent survey would mask unavailability, whether via harvest or abandonment, of individuals from previous surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, daily gobbling activity was negatively related to hunting, and gobbling activity declined precipitously with onset of hunting and harvest of males. We offer that this finding is a consequence not only of the removal of vocal males from the landscape, but also elevated predation risk (hunting activity) prompting males to reduce vocalizations and adopt alternative strategies (e.g., roost at different sites each night to locate receptive females) to secure reproductive opportunities (Wakefield et al ). Collectively, our findings suggest that hunting is an important mediating effect on daily gobbling activity in the turkey population we studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have noted similar fluctuations in daily gobbling activity in wild turkeys (Chamberlain et al , Wightman et al ); hence, we were not surprised to observe a negative relationship between predicted daily gobbling activity relative to gobbling activity the previous day. An alternative, and not mutually exclusive, explanation is that vocal males are moving and roosting away from stationary ARUs on consecutive nights because male wild turkeys exhibit low fidelity to roost sites on consecutive nights during the reproductive season (Byrne et al , Wakefield et al ). However, it is logical to assume that if some males moved away from ARUs to roost on consecutive nights, others would move towards them.…”
Section: Discussionmentioning
confidence: 99%